Quality of Life and Community Wellbeing of Members Associated With Village Savings and Loans Associations as a Model of Sharing Economy in the Least Developing Countries: A Case of Mzuzu City in Northern Malawi, Southern Africa - Wu, Xue-Lian; Munthali, George N. Chidimbah; Dzimbiri, Mastano N. Woleson; Aakash, Abdur Rahman; Rizwan, Muhammad; Shi, Yu; Daru, Gama Rivas; Sheferaw, Wegayehu Enbeyle (Frontiers in Psychology, 2022)
This study was aimed at examining the impacts of the Sharing economy on the individual and community Quality of Life (QOL) and well-being by looking at their associated influencing factors using Village Savings and Loans Associations as a model of sharing economy in Malawi. An online community-based cross-sectional study design was conducted from November 2020 through January 2021. 402 VSLAs members from the Mzuzu City area participated in the survey, recruited using snowball and respondent-driven sampling techniques. The sample size was computed using a single population proportion using the Yamane formula. Descriptive statistics and ordinal logistic regression model techniques were also employed. Additionally, we used the Chi-Square test, two-way ANOVA, and Ordinal regression model to determine statistical associations between socioeconomic data and QOL and well-being variables with a 5% level of significance. On the aspect of community well-being, the findings of our study indicated that income (levels and disposal) provided members with options to live a better QOL and well-being within the community by either facilitating payment for better education, eating healthier foods, acquiring assets, etc. Further, the absence of discrimination provided a platform for voice, inclusion, and social trust, enhancing freedom of expression. We also found that education facilitated better earnings and knowledge of public health-related issues. As for the contribution to the sharing economy, our study has emphasized the role played by trust in enhancing sharing economy. We recommend and encourage people to join these VSLAs so as to improve their QOL and well-being. However, there is a need to replicate the study on a larger scale to validate our study findings for effective policy formulation and implementation geared to improving the overall quality of people’s lives. Based on these findings, we further recommend that authorities reinstate programs like National Strategy for Financial Inclusion 2016-2020 and Savings and Loan Groups Best Practice Guidelines (SLG BPGs) 2016-2017 that could further enhance the future of VSLAs, which are vital for QOL and community well-being of the people in developing countries like Malawi.